Solvent Evaporation Method and Crystal Structure of 2-[5-(1H-benzo[d]imidazol-2-yl)pyridin-3-yl]-1H-benzo[d]imidazole - He, Y.X. (Asian Journal of Chemistry, 2015)
One new benzimidazole compound i.e., 2-[5-(1H-benzo[d]imidazol-2-yl)pyridin-3-yl]-1Hbenzo[ d]imidazole with m.f. C22H17N6O2 was synthesized with pyridine-3,5-dicarboxylic acid, benzene-1,2-diamine and polyphosphoric acid. The compound has been characterized by X-ray single-crystal diffraction. The compound shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding connection.